Site specific Co(iii) sarcophagine binding in multi-component phosphonium and p-sulfonatocalix[4]arene systems - Ling, Irene; Alias, Yatimah; Sobolev, Alexandre N.; Skelton, Brian W.; Raston, Colin L. (Royal Society of Chemistry, 2011)
Co(iii) sarcophagine-type cage molecules, [Co(diCLsar)](3+) or [Co(HONOsar)](3+), form either 1 : 1 or 1 : 2 host-guest inclusion complexes with mono-phosphonium cations and sodium p-sulfonatocalix[4]arene in the solid state yielding complex I [p-sulfonatocalix[4]arene·Co(diCLsar)·2{benzyltriphenylphosphonium}], complex II [2{p-sulfonatocalix[4]arene}·Co(diCLsar)· {tetraphenylphosphonium}] and complex III [p-sulfonatocalix[4]arene·Co(HONOsar)·tetraphenylphosphonium]. The diversity of the structural types of these multi-component systems, including the orientation of the Co(iii) molecules in the cavities of the calixarenes, depends on the nature of their terminal functional groups. The secondary coordination interactions binding between the Co(iii) molecules and p-sulfonatocalix[4]arene have also been investigated in water using NMR techniques.